2017
DOI: 10.7448/ias.20.1.21162
|View full text |Cite
|
Sign up to set email alerts
|

How common and frequent is heterosexual anal intercourse among South Africans? A systematic review and meta‐analysis

Abstract: Background: HIV is transmitted more effectively during anal intercourse (AI) than vaginal intercourse (VI). However, patterns of heterosexual AI practice and its contribution to South Africa’s generalized epidemic remain unclear. We aimed to determine how common and frequent heterosexual AI is in South Africa. Methods: We searched for studies reporting the proportion practising heterosexual AI (prevalence) and/or the number of AI and unprotected AI (UAI) acts (frequency) in South Africa from 1990 to 2015. Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 104 publications
2
25
0
Order By: Relevance
“…Although scarce, the available data on AI frequency suggests that AI is practised frequently, with 2.4-15.9% of all intercourse acts being anal among all FSW study participant samples. Similar to previous review findings regarding heterosexual AI practice among young people and South Africans [37,38], we found a non-statistically significant indication that AI prevalence may have increased over time. In qualitative research Indian and East African FSW have described AI practice during sex work as becoming more common over time due to increased client demand [9,[39][40][41].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Although scarce, the available data on AI frequency suggests that AI is practised frequently, with 2.4-15.9% of all intercourse acts being anal among all FSW study participant samples. Similar to previous review findings regarding heterosexual AI practice among young people and South Africans [37,38], we found a non-statistically significant indication that AI prevalence may have increased over time. In qualitative research Indian and East African FSW have described AI practice during sex work as becoming more common over time due to increased client demand [9,[39][40][41].…”
Section: Discussionsupporting
confidence: 87%
“…AI is a highly stigmatised behaviour in many societies and thus its reporting is likely subject to social desirability bias and is likely more accurately reported using more confidential interview methods [37,38]. As the majority of studies in this review used FTFI, the least confidential interviewing method, our pooled estimates of AI prevalence and estimates of AI frequency likely underestimate its practice among FSW.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Trends in prevalence and frequency of heterosexual anal intercourse may affect trends in population‐level sexual risks, which further depends on condom use during anal intercourse. This is may be to be lower than for vaginal intercourse , although a systematic review of South Africa indicated equal or higher condom use during anal intercourse . Some studies suggest that heterosexual anal intercourse has become more common over time but, generally, trends in heterosexual anal intercourse in sub‐Saharan Africa are poorly understood and impacts of different types of sexual intercourse on population‐level sexual risks could not be evaluated in this study.…”
Section: Discussionmentioning
confidence: 89%